INCREASING THE BIOMASS OF ANKISTRODESMUS MICROALGAE IN CHU-13 FOOD ENVIRONMENT FOR AQUACULTURE (Scientific journal of the Fergana State University, 2024)
As the world population grows, so does the demand for aquaculture feed. For this reason, the biomass of the microalga Ankistrodesmus was increased on the CHu-13 nutrient medium and its dry biomass was determined.